Diversity and distribution of bamboo‐feeding true bugs in China - Kun Jiang; Juhong Chen; Shujing Wang; Yanfei Li; Danli Zhang; Haoyuan Hu; Wenjun Bu (Ecology and Evolution, 2024)
Abstract The Bambusoideae subfamily, originating in the late Cretaceous, has evolved to include over 1500 species globally. Notably, China hosts the richest diversity of Bambusoideae, with 728 species documented. After a long period of coevolution, plenty of animals could feed on these plants rich in cellulose and lignin. As an important group of pests and participants in the ecosystem, bamboo‐feeding true bugs (BFTBs, or bamboo‐feeding Heteropteran insects) have attracted the attention of researchers. However, the diversity and distribution of BFTBs still lack systematic and generalized research. In this study, we reviewed the BFTBs in China and simulated the diversity pattern and the driving forces of this pattern. A list of 36 genera with 69 species of BFTBs in China was obtained through paper review and field surveys. And their bamboo‐feeding habit had multiple independent origins. The spatial diversity pattern showed that the biodiversity hotspots of BFTBs are located in and around the tropics of southern China. Environmental driving force analysis showed that the minimum temperature of coldest month and annual precipitation were the dominant environmental factors shaping the spatial diversity of BFTBs. Our work quantified the diversity and distribution of BFTBs in China, providing fundamental data support for pest control and evolutionary research.